2020
DOI: 10.1002/smll.201906380
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Activation Mechanism and Boosting Electrocatalytic Activity of Layered Perovskite Ruthenate

Abstract: SrRuO3 as a rare conductive perovskite ruthenate has attracted increasing attention for application in energy conversion. Here, the electrocatalytic activity for the hydrogen evolution reaction (HER) of thermally synthesized layered SrRuO3 is investigated and shows a considerable activation during cathodic polarization in alkaline solution. The analysis demonstrates the electrode activation is caused by the increased hydrophilicity of SrRuO3 surface, revealing the influence of the surface properties on HER per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
(38 reference statements)
1
20
0
Order By: Relevance
“…[4,42] For the C 1s spectrum of RCO/Co 3 O 4 -350 DSHPs in Figure S17A (Supporting Information), three peaks are allocated to CO (288.5 eV), CO (286.6 eV), and CC/ CC (284.8 eV), and the peak at 282.0 eV is corresponding to the Ru 3d 5/2 of Ru 4+ . [19,41] The O 1s spectrum (Figure S17B, Supporting Information) is fitted to four oxygen contributions and the following peaks at 529.5 and 530.0 eV can be attributed to Ru-O and Co-O bands, [19,43] respectively. Furthermore, the peak at 531.1 eV is usually associated with O-vacancy, O-H and chemisorbed oxygen (O ad ), [8,10] and the peak at 532.5 eV is corresponding to the physicochemical absorbed H 2 O at the surface of catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4,42] For the C 1s spectrum of RCO/Co 3 O 4 -350 DSHPs in Figure S17A (Supporting Information), three peaks are allocated to CO (288.5 eV), CO (286.6 eV), and CC/ CC (284.8 eV), and the peak at 282.0 eV is corresponding to the Ru 3d 5/2 of Ru 4+ . [19,41] The O 1s spectrum (Figure S17B, Supporting Information) is fitted to four oxygen contributions and the following peaks at 529.5 and 530.0 eV can be attributed to Ru-O and Co-O bands, [19,43] respectively. Furthermore, the peak at 531.1 eV is usually associated with O-vacancy, O-H and chemisorbed oxygen (O ad ), [8,10] and the peak at 532.5 eV is corresponding to the physicochemical absorbed H 2 O at the surface of catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various hybrid HER electrocatalysts with heterojunction, Ru oxide is rarely discussed, and only few reports show that the heterojunction based on Ru oxide possesses superior HER activity. [8,19] Moreover, compared with simple nanoparticle or bulk structures, the proper construction of special nano-structures, especially the hollow structure, is also conducive to improve the catalytic activity of electrocatalyst. [20,21] To be specific, hollow structure with high surface area supplies sufficient active sites for surface-related reactions, such as surface redox reaction and adsorption/desorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new peak occurred at ∼529.3 eV in the O 1s spectrum after OER, which belongs to the lattice oxygen (Figure S14f). , These data indicate that an amorphous CoOOH layer might be formed on the surface of NiCo-CHS during the OER test.…”
Section: Resultsmentioning
confidence: 99%
“…Despite considerable efforts, the OER/HER electrocatalytic performances of most perovskite oxides are still inferior to those of commercial IrO 2 /RuO 2 or Pt/C catalysts. Recent studies have shown that doping a small number of precious metals (i.e., Pt, Ru, and Ir) in perovskites can significantly improve their activity and stability [61,[112][113][114][115]. For instance, Wang et al prepared a series of LaCo 1-x Pt x O 3-δ (× = 0, 0.02, 0.04, 0.06, and 0.08) perovskite oxides.…”
Section: Performance Improvement Strategies Of Perovskite Oxides For ...mentioning
confidence: 99%